Barriers to digitization in university libraries of Pakistan: a developing country’s perspective - Rafiq, Muhammad; Ameen, Kanwal; Jabeen, Munazza (Electronic library, 2018)
Purpose The purpose of this study is to identify barriers that are hindering digitization initiatives in university libraries of Pakistan. Design/methodology/approach The study opted a mixed-methods research design based on quantitative (QUAN) and qualitative (QUAL) strands by using a survey research method. The subjects of the study were central libraries of the universities (both public and private sector) of Pakistan. A self-administered structured questionnaire was used for QUAN data collection in the QUAN strand. In the QUAL phase, in-depth interviews of purposely selected 25 library experts from different parts of the country were conducted. Findings Meta-inferences were drawn from the findings of both QUAN and QUAL strands. Both of the research designs provided the requisite data to answer research questions of the study. The finding revealed the barriers which were hindering the digitization activities in university libraries of Pakistan. Originality/value The findings of the study are helpful for funding bodies, university libraries and university administration. The findings are also helpful for other developing countries with similar economic and/or social landscapes.